The man in the Rockefeller suit : the astonishing rise and spectacular fall of a serial impostor - Seal, Mark, 1953- (New York : Viking, 2011)
A probing and cinematic exploration of an audacious impostor, Christian Gerhartsreiter, and his "talented Mr. Ripley" story as Clark Rockefeller.
The unbelievable thirty-year run of a shape-shifting con man. Clark Rockefeller's story is a strange twist on the classic American success story of the self-made man--because Clark Rockefeller was totally made up. Born in a small village in Germany, Christian Karl Gerhartsreiter was obsessed with getting to America. At seventeen, he flew into the country on dubious student visa documents. Over the next thirty years, boldly assuming a series of false identities, he moved up the social ladder across the country--culminating in a twelve-year marriage to a Harvard MBA who believed she'd wed a Rockefeller. The imposter charmed his way into exclusive clubs and financial institutions--working on Wall Street, showing off an extraordinary art collection--until his marriage ended and he was arrested for kidnapping his daughter, which exposed his past of astounding deceptions as well as a chilling connection to the bizarre mid-1980s disappearance of a California couple.--From publisher description.
Christian Karl Gerhartsreiter : Bergen, Germany -- Strangers on a train -- Becoming American -- Christopher Chichester : San Marino, California -- The secret mission -- Christopher Crowe : Greenwich, Connecticut -- Wall Street -- Missing persons -- Clark Rockefeller : New York, New York -- Sandra -- "San Marino bones"-- The last will and testament of Didi Sohus -- The country squire -- Snooks -- The god of war -- The Boston Brahmin -- Peach Melba nights -- "Find out who he is" -- Chip Smith : Baltimore, Maryland -- The manhunt -- One last con?
Keywords: Gerhartsreiter, Christian, -- 1961-; Impostors and imposture -- Case studies. -- United States